Heuristic trust-based neighbour centric routing for CPS-enabled wireless sensor and ad hoc network. (27th August 2021) - Singhal, Chetna; Rajesh, A.
Security in cyber physical system (CPS)-enabled wireless sensor and ad hoc network (WSN) is carried out using trustworthy intermediate neighbour nodes, through which sensed information can be securely dispatched to the destination. In this paper, we propose a trust dependent routing scheme to select the most secure routes in such network, which focuses on evaluating any neighbouring entity through direct and indirect trust opinion. Trust assessment is carried out on neighbours by various trust metrics, namely, packet delivery ratio, delay, throughput, topology, energy, and control packets. Initially, we developed the trust-based neighbour centric routing (TBNCR) algorithm for static CPS-enabled WSN. At a later stage, this is further enhanced to meet the dynamic challenges of mobile ad hoc network (MANET) and also tested with various network density and probable security threats. Our simulation reveals that the proposed TBNCR protocol achieved almost 10%-15% higher throughput and reduced packet loss when compared with similar works carried out in the literature.